Da explicação pronta à compreensão incerta - Medina, Cremilda (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
In projects such as “The New Pact of Science”, “São Paulo in Profile” and “Permanent Forum for Reflecting upon Latin America”, which were all developed in and out of the University of São Paulo (USP) in the scope of its undergraduate and graduate programs, as well as a program for senior citizens, the author reveals a personal and also collective building of the Relation Sign along her career as a journalist, researcher and professor. Based upon the languages of affections, such sign becomes consistent in the fields of Communication and Journalism through the production of what Medina calls the great narrative of contemporaneity. This path is multi-, inter-, and transdisciplinary path which resulted in the writing of 18 books and the editing of 52 anthologies, as well as the tutoring of 29 Master’s theses, 31 PhD dissertations and the supervision of two postdoctoral research projects. Those are the roots of an epistemological research and practice which became the cradle for the conception of comprehension as a method.